Optimalisasi Manajemen Guru Penggerak dalam Meningkatkan Kompetensi Profesional (Studi Kasus guru SD Negeri Bunikasih 4 Kecamatan Warungkondang Kab. Cianjur) - Suharyanto H. Soro; Maman Suherman; Yusep Saripudin; Tini Kartini; Ani Susilawati (LP. Ma'arif Janggan Magetan, 2024)
The Teacher Mobilization Program was launched by the Ministry of Education and Culture to improve teacher professional competence. This program is a concrete manifestation of the concern of the Government of the Republic of Indonesia in achieving national education goals. Implementation of the teacher mobilization program is still an obstacle in the field, resulting in a negative impact on teacher competency. The aim of this research is to describe the optimization of driving teachers in improving professional competence so that it has a positive impact on the quality of graduates. Researchers use a qualitative research paradigm with a case study approach. Data collection methods use observation, interviews and documentation studies. Sampling was carried out by purposive sampling. Research activities were carried out at SD Negeri Bunikasih 4, Warungkondang District, Cianjur Regency, academic year 2024. Research finding show that increasing teacher professional competence can be done by optimizing the management of inspiring teachers.